The relationship between compliance and compulsion, and dynamics of diversion, in child welfare decision-making. (17th January 2023) - Donnelly, Michelle
Abstract: This article explores the relationship between (parental) compliance and (child) compulsion, within the wider dynamics of diversion, in child welfare decision-making. It examines how notions of parental compliance can be used by decision-makers to distinguish between compulsory and voluntary forms of state intervention in children's and families' lives. The article focusses on Scotland as a case study by drawing on empirical findings from a qualitative investigation into gatekeeping decision-making in the children's hearings system, which found that notions of parental compliance are significant to decisions about whether to bring children within the statutory child protection system in practice. Key findings on parental cooperation, engagement, and acceptance are conceptualised as forms of 'compliance', linked to the existing international evidence base, and analysed in terms of state power and coercion, parental stigma and resistance in child protection processes. The relationship between parental compliance and child compulsion is scrutinised, in light of the procedural peculiarities of the Scottish system and wider proliferation of diversionary strategies aimed at reducing the numbers of children being drawn into formal child protection processes. The conclusion is that positive parental compliance may support diversion from involuntary child protection processes but there should be limits to reliance on negative conceptions of non-compliance to support direction into the statutory system.